2021
DOI: 10.1177/09610006211063202
|View full text |Cite
|
Sign up to set email alerts
|

Information work of hospital librarians: Making the invisible visible

Abstract: The aim of this paper is to explore and to make visible how the information work of hospital librarians is enacted in key practices where services of the hospital library are employed to support evidence-based practice. The empirical material was produced at three hospital libraries in three different regions in Sweden between January and March 2020. A practice-oriented approach using the theoretical lens information work is employed to analyze nine semi-structured interviews with hospital librarians and hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
(74 reference statements)
1
1
0
1
Order By: Relevance
“…This suggests that information use is implicit in discussions and tasks, and may be invisible to both those who undertake it and those who observe it. This is in line with prior work reported by Hanell and Ahlryd (2021) and McKenzie and Dalmer (2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that information use is implicit in discussions and tasks, and may be invisible to both those who undertake it and those who observe it. This is in line with prior work reported by Hanell and Ahlryd (2021) and McKenzie and Dalmer (2020).…”
Section: Discussionsupporting
confidence: 93%
“…In the wider literature, a similar lack of clarity regarding the information-handling demands of jobs and job tasks has been reported, even in occupations known to be particularly information-intensive, such as archival work (Garwood & Poole, 2021). The degree of information seeking performed as part of one's job may be considerable, and yet, to some extent, invisible (Hanell & Ahlryd, 2021; McKenzie & Dalmer, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our results are in line with previous research that has shown that information work is often invisible (Ehrlich and Cash, 1999;Hanell and Ahlryd, 2023;McKenzie and Dalmer, 2020). The theme of invisibility that McKenzie and Dalmer (2020) identify with reference to the location where the work takes place, for example, at home, also occurs in our study.…”
Section: Concluding Discussionsupporting
confidence: 93%
“…In a similar vein, but with a particular focus on the mediation work of librarians, Ehrlich and Cash (1999) identify three perspectives from which library work appears as invisible: to the library visitor 'who has no reason to be aware of the complex skills associated with finding the requested information', within an organisation, and at managerial levels, 'which may lead to misguided attempts to create "better" or "less complex" information management schemes' (p. 151). Hanell and Ahlryd (2023) also employ the concept 'invisible work' in their study of hospital librarians' work. They conclude that a significant portion of their work is invisible to clinicians.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Boudreau et al (2014) ogHanell & Ahlryd (2023). Andre informanter naevnte, at de var blevet ansat til netop at tage sig af fysiske kulturelle aktiviteter og havde derfor kompetencerne til dette, og endelig argumenterede flere, at fysiske aktiviteter i biblioteksrummet var nødvendige, hvis biblioteket skulle overleve:"Jeg har jo selv sådan en kongstanke omkring bibliotekerne, at jeg synes man skal gå efter at møde folk i levende live, fordi det tror jeg er det, der på en eller anden måde bliver bibliotekernes redning, nu lyder det meget dramatisk, men altså nu har jeg ikke vaeret i biblioteksbranchen så laenge, men laenge nok til at fornemme det her med at udlånet falder…" (Interview nr 22).…”
unclassified